2018
DOI: 10.1186/s12967-018-1383-0
|View full text |Cite
|
Sign up to set email alerts
|

TIPE2 suppresses progression and tumorigenesis of esophageal carcinoma via inhibition of the Wnt/β-catenin pathway

Abstract: BackgroundEsophageal carcinoma is the eighth prevalent malignancy and ranks the sixth in carcinoma-related death worldwide. Tumor necrosis factor-α-induced protein-8 like-2 (TIPE2) has been identified as a tumor suppressor in multiple carcinomas. However, its roles and molecular mechanisms underlying esophageal carcinoma progression are still undefined till now.MethodsRT-qPCR assay was employed to detect the expression of TIPE2 mRNA. TIPE2 protein expression was measured by using western blot assay. Ad-V and A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 35 publications
(42 reference statements)
2
19
0
Order By: Relevance
“…The assay was performed by using a Cell-Light™ EdU Apollo 567 In Vitro Imaging Kit (EdU; Guangzhou RiboBio, Guangzhou, China) as described previously [37]. Briefly, 5000 pMSCs were plated into 96-well tissue culture plates for 48 h, and the cells were exposed to EdU at a concentration of 50 μM and incubated for 2 h, followed by fixation with 4% formaldehyde for 30 min.…”
Section: Methodsmentioning
confidence: 99%
“…The assay was performed by using a Cell-Light™ EdU Apollo 567 In Vitro Imaging Kit (EdU; Guangzhou RiboBio, Guangzhou, China) as described previously [37]. Briefly, 5000 pMSCs were plated into 96-well tissue culture plates for 48 h, and the cells were exposed to EdU at a concentration of 50 μM and incubated for 2 h, followed by fixation with 4% formaldehyde for 30 min.…”
Section: Methodsmentioning
confidence: 99%
“…PEDF is a 50 kDa secreted protein which is a versatile member of the widely expressed serpin family, also denoted as SERPINF1 (1). It plays important roles in angiogenesis, fibrogenesis, neuroprotection, bone matrix mineralization, and inflammation (4).…”
Section: Discussionmentioning
confidence: 99%
“…Esophageal carcinoma is a common gastrointestinal cancer that has two major subtypes: adenocarcinoma and squamous cell carcinoma (1). It is the sixth cancer-related deaths worldwide.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…is a tumour suppressor in many types of cancer. [16][17][18][19][20][21] However, the study the intracellular mechanisms of action of therapeutic agents. 39,40,44 In the present study, HR8348 and SW837 cells were used to evaluate the effects of TIPE2 both in vitro and in vivo and A recent study has shown that TIPE2 overexpression could induce cell death and inhibit Ras-mediated tumourigenesis in mice.…”
Section: An Increasing Number Of Studies Have Demonstrated That Tipe2mentioning
confidence: 99%